Prevalence of High-Burden Medical Conditions Among Young and Middle-Aged Adults With Pediatric-Onset Medical Conditions: Findings From US Private and Public Administrative Claims Data - Daniel G. Whitney (Kerman University of Medical Sciences, 2019)
Adults with pediatric-onset medical conditions (POMCs) are susceptible to early development of high-burden medical conditions. However, research pertaining to this topic is lacking, which is vital information that could assist in health benefit planning and administration. The purpose of this study was to determine the prevalence of high-burden medical conditions among privately and publicly insured adults with POMCs, as compared to adults without POMCs, from the US. Data from 2016 were extracted from Optum Clinformatics® Data Mart (private insurance) and a random 20% sample from Medicare fee-for-service (public insurance). International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) diagnosis codes were used to identify 18-64-year-old beneficiaries with POMCs, as well as several high-burden medical conditions, including pain, fracture, mood affective disorders, anxiety disorders, ischemic heart diseases, cerebrovascular diseases, hypertensive and other cardiovascular diseases, type 2 diabetes, osteoporosis, osteoarthritis, chronic obstructive pulmonary diseases, liver diseases, and cancer. Privately and publicly insured adults with POMCs had higher prevalence of all medical conditions compared to adults without POMCs. Publicly insured adults with POMCs had higher prevalence of all medical conditions compared to privately insured adults with POMCs, except for the lower prevalence of pain and cancer. When stratified by the category of POMCs (eg, musculoskeletal, circulatory), privately and publicly insured groups tended to have higher prevalence of most (private) or all (public) medical conditions compared to adults without POMCs. Adults with POMCs have higher prevalence of several high-burden medical conditions compared to adults without POMCs. This health disparity was present regardless of insurance coverage, but was generally more pronounced for public vs. private insured adults with POMCs.